Enhancing In Vitro Production of the Tree Fern Cyathea delgadii and Modifying Secondary Metabolite Profiles by LED Lighting - Wojciech Tomaszewicz; Monika Cioć; Katarzyna Dos Santos Szewczyk; Małgorzata Grzyb; Wioleta Pietrzak; Bożena Pawłowska; Anna Mikuła (Cells, 2022)
The tree ferns are an important component of tropical forests. In view of this, the enhancement of in vitro production of these plants is needed. Thus, the effect of different light-emitting diodes (LEDs) as well as control fluorescent lamps (Fl) and a 3-week-long period of darkness at the beginning of in vitro culture on micropropagation of the tree fern Cyathea delgadii Sternb. was analysed. Moreover, the photosynthetic pigment content and secondary metabolite profiles were estimated. The period of darkness contributed to a high production of somatic embryo-derived sporophytes and a low production of gametophytes. The formation of new sporophytes was stimulated by RBY (35% red, 15% blue, and 50% yellow) and B (100% blue) lights when the stipe explants or whole young sporophytes were used in the culture, respectively. The elongation of the roots and leaves was stimulated by RBfR light (35% red, 15% blue, and 50% far red), while root production increased under RBY light. The RB (70% red and 30% blue) and B lights stimulated the accumulation of chlorophyll better than Fl light. The most abundant metabolite found in the plant extracts was trans-5-O-caffeoylquinic acid (1.013 µg/mg of dry weight). The extract obtained from plants growing in a greenhouse had the best antioxidant activity.